51.8k views
2 votes
Kindly help with this Surd question

Kindly help with this Surd question-example-1

2 Answers

5 votes
Answer: 1/sqrt(2) + 1

Step-by-step explanation:

(1 + sqrt(2))/sqrt(2)
= 1/sqrt(2) + sqrt(2)/sqrt(2)
= 1/sqrt(2) + 1
User Vignesh KM
by
6.2k points
4 votes

Answer:

Step-by-step explanation:

Rationalize the denominator, to do that multiply denominator and numerator by √2


(1+√(2))/(√(2))=((1+√(2))*√(2))/(√(2)*√(2))\\\\ =(1*√(2)+√(2)*√(2))/(√(2*2))\\\\\\=(√(2)+2)/(2)\\\\\\

User Gkapoor
by
6.0k points